Nutraceutical Profiles of Two Hydroponically Grown Sweet Basil Cultivars as Affected by the Composition of the Nutrient Solution and the Inoculation With Azospirillum brasilense - Kolega, Simun; Miras-Moreno, Begona; Buffagni, Valentina; Lucini, Luigi; Valentinuzzi, Fabio; Maver, Mauro; Mimmo, Tanja; Trevisan, Marco; Pii, Youry; Cesco, Stefano (Frontiers in Plant Science, 2020)
Sweet basil (Ocimum basilicum L.) is one of the most produced aromatic herbs in the World, exploiting hydroponic systems. It has been widely assessed that macronutrients, like nitrogen (N) and sulphur (S), can strongly affect the organoleptic qualities of agricultural products, thus influencing their nutraceutical value. Also, plant growth-promoting rhizobacteria (PGPR) have been shown to effect plant growth and quality. Azospirillum brasilense is a PGPR able to colonize the root system of different crops, promoting their growth and development and influence the acquisition of mineral nutrients. On the bases of these observations, we aimed at investigating the impact of both mineral nutrients supply and rhizobacteria inoculation on the nutraceutical value on two different sweet basil varieties, i.e., Genovese and Red Rubin. To these objectives, basil plants have been grown in hydroponics, with nutrient solutions fortified for the concentration of either S or N, supplied as SO42- or NO3-, respectively. In addition, plants were either non-inoculated or inoculated with A. brasilense. At harvest, basil plants were assessed for the yield and the nutraceutical properties of the edible parts. The cultivation of basil plants in the fortified nutrient solutions showed a general increasing trend in the accumulation of the fresh biomass, albeit the inoculation with A. brasilense did not further promote the growth. The metabolomic analyses disclosed a strong effect of treatments on the differential accumulation of metabolites in basil leaves, producing the modulation of more than 400 compounds belonging to the secondary metabolism, as phenylpropanoids, isoprenoids, alkaloids, several flavonoids, and terpenoids. The primary metabolism resulted also influenced by the treatments showing changes in the fatty acid, carbohydrates, and amino acids metabolism. The amino acid analysis revealed that the treatments induced an increase in the leaves content of arginine (Arg), which has been shown to have beneficial effects on human health. In conclusion, between the two cultivars studied, Red Rubin displayed the most positive effect in terms of nutritional value, which was further enhanced following A. brasilense inoculation.